Asymmetric dimethylarginine, related arginine derivatives, and incident atrial fibrillation - Schnabel, Renate B.; Maas, Renke; Wang, Na; Yin, Xiaoyan; Larson, Martin G.; Levy, Daniel; Ellinor, Patrick T.; Lubitz, Steven A.; Mcmanus, Davidd.; Magnani, Jared W.; Atzler, Dorothee; Boeger, Rainer H.; et al. (American Heart Journal, 2016)
Oxidative stress plays an important role in the development of atrial fibrillation (AF). Arginine derivatives including asymmetric dimethylarginine (ADMA) are central to nitric oxide metabolism and nitrosative stress. Whether blood concentrations of arginine derivatives are related to incidence of AF is uncertain.In 3,310 individuals (mean age 58 ± 10 years, 54% women) from the community-based Framingham Study, we prospectively examined the relations of circulating levels of ADMA, l-arginine, symmetric dimethylarginine (SDMA), and the ratio of l-arginine/ADMA to incidence of AF using proportional hazards regression models. Over a median follow-up time of 10 years, 247 AF cases occurred. Using age- and sex-adjusted regression models, ADMA was associated with a hazard ratio of 1.15 per 1-SD increase in loge-biomarker concentration (95% CI 1.02-1.29, P = .02) for AF, which was no longer significant after further risk factor adjustment (hazard ratio 1.09, 95% CI 0.97-1.23, P = .15). Neither l-arginine nor SDMA was related to new-onset AF. A clinical model comprising clinical risk factors for AF (for age, sex, height, weight, systolic blood pressure, diastolic blood pressure, current smoking, diabetes, hypertension treatment, myocardial infarction, and heart failure; c statistic = 0.781; 95% CI 0.753-0.808) was not improved by the addition of ADMA (0.782; 95% CI 0.755-0.809).Asymmetric dimethylarginine and related arginine derivatives were not associated with incident AF in the community after accounting for other clinical risk factors and confounders. Its role in the pathogenesis of AF needs further refinement.
EVALuna2:8703